Strigolactone hormones and their stereoisomers signal through two related receptor proteins to induce different physiological responses in arabidopsis - Scaffidi, A.; Waters, M.; Sun, Y.; Skelton, B.; Dixon, Kingsley; Ghisalberti, E.; Flematti, G.; Smith, S. (American Society of Plant Biologists, 2014)
Two a/ß-fold hydrolases, KARRIKIN INSENSITIVE2 (KAI2) and Arabidopsis thaliana DWARF14 (AtD14), are necessary for responses to karrikins (KARs) and strigolactones (SLs) in Arabidopsis (Arabidopsis thaliana). Although KAI2 mediates responses to KARs and some SL analogs, AtD14 mediates SL but not KAR responses. To further determine the specificity of these proteins, we assessed the ability of naturally occurring deoxystrigolactones to inhibit Arabidopsis hypocotyl elongation, regulate seedling gene expression, suppress outgrowth of secondary inflorescences, and promote seed germination. Neither 5-deoxystrigol nor 4-deoxyorobanchol was active in KAI2-dependent seed germination or hypocotyl elongation, but both were active in AtD14- dependent hypocotyl elongation and secondary shoot growth. However, the nonnatural enantiomer of 5-deoxystrigol was active through KAI2 in growth and gene expression assays. We found that the four stereoisomers of the SL analog GR24 had similar activities to their deoxystrigolactone counterparts. The results suggest that AtD14 and KAI2 exhibit selectivity to the butenolide D ring in the 2'R and 2'S configurations, respectively. However, we found, for nitrile-debranone (CN-debranone, a simple SL analog), that the 2'R configuration is inactive but that the 2'S configuration is active through both AtD14 and KAI2. Our results support the conclusion that KAI2-dependent signaling does not respond to canonical SLs. Furthermore, racemic mixtures of chemically synthesized SLs and their analogs, such as GR24, should be used with caution because they can activate responses that are not specific to naturally occurring SLs. In contrast, the use of specific stereoisomers might provide valuable information about the specific perception systems operating in different plant tissues, parasitic weed seeds, and arbuscular mycorrhizae.